Chryzantema Miyazakiego. Antywojenne idee w anime Zrywa się wiatr - Czajka, Łukasz (Sensus Historiae, 2025)
The starting point for the considerations presented in this article is Ruth Benedict’s thesis on the dualism of Japanese culture, symbolically represented by the “chrysanthemum” and the “sword.” The main research objective is to confirm the initial hypothesis indicating that the work of Japanese animator Miyazaki Hayao represents the “chrysanthemum.” To fulfill the research task, an in-depth content interpretation of the anime The Wind Rises was carried out, supplemented by references to the artist’s entire oeuvre. These analyses are reinforced by references to numerous socio-political commentaries on Japan's imperial past and current disputes over revising the Japanese constitution. All these ideas form the core of pacifist anti-war thought, inscribing Miyazaki on the chrysanthemum side of Japanese culture.